Analysis Of The Variables Of Intention Of The Adoption And Acceptance Of Artificial Intelligence And Big Data Tools Among Leaders Of Organizations In Morocco: Attempt Of A Theoretical Study - Yousra, Moudni; Khalid, Chafik (European Scientific Journal, ESJ, 2021)
Artificial intelligence and big data are two emerging technologies that is now gaining ground among organizations. Their added value and their impact on business performance differ from one industry to another. Due to increased competitiveness, and in order to survive in the market, companies are led to adopt these new technologies that will enable them to be more performant and offer customers goods or services that meet their real needs since this approach is based on data collected from outside the company’s environment. To do so, it is important to know and analyze beforehand the factors and variables that impact the adoption and acceptance process in order to manage them. This paper focuses on establishing a synthetic literature review to find out the current state of researches on the problems of AI and Big data adoption and acceptance, and it also argument the empirical sector’s choice. The findings of this study show that agricultural and chemical industry sectors are the two most promising sectors for AI in Morocco. As a result, a comparative analysis will be conducted after the development of the research model on these two fields in order to analyze the variables of adoption and acceptance of AI. Also, the most influential variables according to the literature were detected in this paper, which are grouped into four (4) types: technological, organizational, environmental, and behavioral variables.